Systematic Literature Review of the Use of Computational Intelligence in the Routing and Spectrum Assignment Problem in Elastic Optical Networks - Renan V. B. Carvalho; Henrique A. Dinarte; Raul C. Almeida Jr.; Carmelo J. A. Bastos-Filho (Journal of Microwaves, Optoelectronics and Electromagnetic Applications)
Abstract Elastic optical networks (EONs) have characteristics that meet the growing demand for current and future bandwidth, such as 5G and Internet of Things. In EONs, connections must have a route and a spectrum slice available between the nodes to establish communication. The process associated with this task is named routing and spectrum allocation (RSA) problem. The RSA problem is NP-hard and several approaches have been proposed in the literature using computational intelligence (CI). This paper provides a systematic literature review (SLR) regarding applying CI to solve the RSA problem in EONs. We offer a research roadmap encouraging the community to address identified limitations and open questions requiring further investigation. This study selects 40 primary studies for analysis and data extraction out of the 659 initially obtained papers. The main conclusions indicate that the community still needs to explore the RSA problem with the freedom to solve it without considering a fixed order of the two subproblems: routing and spectrum allocation. The studies reveal that efficient solutions are achieved with the techniques used in the RSA problem, which made them excellent tools. Furthermore, this SLR presents a set of open questions, suggesting valuable topics for future research through a research guide.